"I Can Actually Be a Super Sleuth": Promising Practices for Engaging Adolescent Girls in Cybersecurity Education. (March 2017) - Jethwani, Monique M.; Memon, Nasir; Seo, Won; Richer, Ariel
Utilizing qualitative data gleaned from focus groups with adolescent girls participating in a cybersecurity summer program ( N = 38, mean age = 16.3), this study examines the following research questions: (a) How do adolescent girls perceive the cybersecurity field? (b) What are the promising practices that engage girls in cybersecurity education? Guided by ecological and social role theories, findings reveal that single-sex collaborative settings with encouraging and supportive teachers and female mentors are practices that contribute to girls' increased interest in the field of cybersecurity. Findings also suggest that an emphasis on creative and collaborative problem-solving processes and the real-world application inherent to cybersecurity are likely to increase girls' engagement in the field. Results have implications for educators, researchers, and policy makers aiming to close gender gaps in the field of computer science and build interest in cybersecurity, an area of critical national need.